1995
DOI: 10.1212/wnl.45.2.393-a
|View full text |Cite
|
Sign up to set email alerts
|

Cataplexy associated with midbrain lesion

Abstract: Disruptive agitated behavior is common in demented patients and is often diEcult to manage.' Although neuroleptic medications are frequently administered to agitated patients, these agents only help in about one-third of cases, and their utility is limited by serious side effects.' A specific cause of agitated behavior in a demented patient is often not identified, and the behavior may sometimes be related to pain or discomfort from an unrecognized medical problem. In this report, we describe a demented woman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Animal studies have demonstrated a prominent role of the brain stem and hypothalamus in the regulation of sleep and wakefulness and have led to the identification of neural generators and modulators of REM sleep in the dorsolateral pons and medial medulla oblongata [2,18,27,30,32,36]. In man, several case studies have reported symptomatic narcolepsy following acquired diencephalic lesions [3,29,34] and brain stem lesions of midbrain [4,10,23,37], pontine [23,24,31,33] and medullary [8] location. However, not all of these cases exhibited a classic narcoleptic syndrome, and some did not meet all diagnostic criteria of narcolepsy according to the International Classification of Sleep Disorders (ICSD).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated a prominent role of the brain stem and hypothalamus in the regulation of sleep and wakefulness and have led to the identification of neural generators and modulators of REM sleep in the dorsolateral pons and medial medulla oblongata [2,18,27,30,32,36]. In man, several case studies have reported symptomatic narcolepsy following acquired diencephalic lesions [3,29,34] and brain stem lesions of midbrain [4,10,23,37], pontine [23,24,31,33] and medullary [8] location. However, not all of these cases exhibited a classic narcoleptic syndrome, and some did not meet all diagnostic criteria of narcolepsy according to the International Classification of Sleep Disorders (ICSD).…”
Section: Introductionmentioning
confidence: 99%
“…Known associations include variant forms of Niemann Picks disease. Pontomedullary lesions causing cataplexy have been described in one case each of multiple sclerosis, a pontine astrocytoma [2] and midbrain toxoplasmosis [3]. Continuous cataplexy has been described in association with a mesencephalic tumour [9].…”
mentioning
confidence: 99%
“…These symptoms were previously described in patients with lesions involving the ponto mesencephalic tegmental area [11][12][13][14][15][16][17], Episodic dysregulation of postural tone in the rostral brainstem reticular formation could be responsible for both of the svmptoms [13].…”
Section: Discussionmentioning
confidence: 90%